Ο ρόλος των μέσων στην ευαισθητοποίηση των πολιτών για την κλιματική αλλαγή - Σακκά Ηλιάνα (Open Journal of Animation, Film and Interactive Media in Education and Culture [AFIMinEC], 2022)
Climate change is one of the most crucial matters of our era. The role of the media has been characterized as more vital than ever in communicating climate change and influencing social concerns. The media also has the unique ability to promote social changes due to journalists presenting alternative and novel ways of social actions. In this paper by conducting a content analysis on the television program, clime, we investigate whether this show has been involved in and deconstructed climate’s hot issues. Clime tries to approach these issues implying the basic rules of environmental education. However, the impact of the climate crisis requires more TV shows, which can focus on the conversion of scientific knowledge to knowledge for the audience. In this way, shows can be educational tools for the benefit of society. The project’s question: Can Clime be the channel of environmental education and awareness, the most motivational forces of making changes?